1998
DOI: 10.2307/3237267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive harvesting on forest floor properties in Betula papyrifera stands in Newfoundland

Abstract: Abstract. Betula papyrifera (White birch) is a common tree throughout the boreal forest of Canada; makes up 12% of the total tree volume in insular Newfoundland. It forms pure stands after harvesting and wildfire disturbance and it is a common component in most softwood stands. Little is known regarding the environmental impact of whole‐tree or conventional harvesting of this species and variation in impact related to variation in soil and site conditions. This study investigates litter and organic matter pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Under conifers light levels are lower on average and there is less seasonal variation in understory light than below broadleaf canopies (Ross et al, 1986;Constabel and Lieffers, 1996;Messier et al, 1998). Broadleaf and conifer species also differ in their litter quality and quantity and thus in their influence on pH, rate of decomposition, and nutrient cycling in forests (Roberts et al, 1998;Paré and Bergeron, 1996;Ste-Marie and Paré, 1999;Hannam et al, 2004). Prior studies have found that the proportion of broadleaf and conifer trees in the canopy influences understory diversity and composition (Berger and Puettmann, 2000;Jobidon et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Under conifers light levels are lower on average and there is less seasonal variation in understory light than below broadleaf canopies (Ross et al, 1986;Constabel and Lieffers, 1996;Messier et al, 1998). Broadleaf and conifer species also differ in their litter quality and quantity and thus in their influence on pH, rate of decomposition, and nutrient cycling in forests (Roberts et al, 1998;Paré and Bergeron, 1996;Ste-Marie and Paré, 1999;Hannam et al, 2004). Prior studies have found that the proportion of broadleaf and conifer trees in the canopy influences understory diversity and composition (Berger and Puettmann, 2000;Jobidon et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Partial harvesting has several possible ecological objectives: (1) preserve species associated with mature forest (''life-boat effect''); (2) move mature forest towards the structure and biotic composition of old forest; (3) achieve a certain desired structural and compositional state supportive of particular biota; (4) leave a biological legacy to support faster post-harvest recovery of biodiversity. The effects of clearcutting on vegetation communities have been well studied in many forest types (Harvey and Bergeron, 1989;Carleton and MacLellan, 1994;Morris and Boerner, 1998;Roberts et al, 1998) and there has been increasing interest in understanding understory responses to partial harvesting (Reader and Bricker, 1992;North et al, 1996;Halpern et al, 1999;Battles et al, 2001;Deal, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Concerns are being raised about the ecological effects of post-fire salvage harvesting (Lindenmayer et al, 2004;Nappi et al, 2004;Donato et al, 2006;Schmiegelow et al, 2006). While a number of studies have documented the impact of forest harvesting in northern forests, often comparing it to fire (Harvey and Bergeron, 1989;Carleton and MacLellan, 1994;Morris and Boerner, 1998;Roberts et al, 1998;Reich et al, 2001;Haeussler and Bergeron, 2004), there is a paucity of information on the impacts of post-fire salvage harvesting (McIver and Starr, 2001; but see studies cited below). Mounting evidence and common sense, however, suggest that salvage harvesting of burnt forest can result in environmental conditions, successional trajectories, and biotic communities that are quite different from those found in burnt, unsalvaged forest (Nappi et al, 2004;Purdon et al, 2004;Hanson and Stuart, 2005;Schmiegelow et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Monitoring the characteristics of a tree stand is much easier than monitoring soil properties, because the dimensions of tree stems are systematically larger after every growing season, unlike most soil properties. Soil parameters may have trends, but may also show unsystematic annual, seasonal and human-induced (cuttings, sampling) variation (Kilian1981; Lockman and Molloy 1984;Lundell 1987;Ilvesniemi 1991;Roberts et al 1998;Tamminen and Derome 2005). During the past 50 years, soil sampling, pretreatment and analyses have varied considerably.…”
Section: Introductionmentioning
confidence: 99%